2018
DOI: 10.1101/471722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylation modules associate with incident cardiovascular disease and cumulative risk factor exposure

Abstract: Background Epigenome-wide association studies using DNA methylation have the potential to uncover novel biomarkers and mechanisms of cardiovascular disease (CVD) risk. However, the direction of causation for these associations is not always clear, and investigations to-date have generally failed to replicate at the level of individual loci. Here, we undertook module-and region-based DNA methylation analyses of incident CVD in the Women's Health Initiative (WHI) and Framingham Heart Study Offspring Cohort (FHS)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Furthermore, it is difficult to assess causality between DNA methylation age acceleration and outcome. As such, additional methods to establish causal relationships have been utilized to explore the causality [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is difficult to assess causality between DNA methylation age acceleration and outcome. As such, additional methods to establish causal relationships have been utilized to explore the causality [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria for participation in the WHI study have been described [17]. From the overall WHI cohort, a stratified, racially/ethnically diverse sample of 2200 WHI clinical trial participants with available stored serum were selected for DNA methylation analysis at either the screening visit or annual visits [15]. A description of the clinical trials has been published [17].…”
Section: Study Populationmentioning
confidence: 99%
“…Nakatochi et al (2017) also performed an EWAS analyses on blood DNA of patients suffering from MI which revealed three differentially methylated CpG sites in SGK1, SMARC4, and ZFHX3. A large EWAS study on the Women's Health Initiative (discovery set) and Framingham Heart Study (FHS) -(replication set) identified three DMRs in SLC9A1, SLC1A5, and TNRC6C linked to CVD incidence (Westerman et al, 2018). The authors also performed a module based epigenetic analysis, which revealed three modules associated with CVD and its risk factors out of which two had strong concordance in both cohorts (Westerman et al, 2018).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Hypomethylation of a specific fragment of CGI-associated HLA-G gene positively correlated with coronary calcium score and was predictive for disease severity suggesting that methylation might not only have a critical role in disease severity but also a role as noninvasive biomarker(s) improving the prognostic value of CCTA [ 116 ]. The WGCNA and Comb-p algorithms have been applied to the identification of blood-based differentially methylated regions (DMRs) and disease modules associated with incident CHD events in two independent cohorts (discovery set: 2129 women, replication set: 2726 subjects) [ 137 ]. This study has identified two modules highly enriched for development and immune-related processes.…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%
“…In addition, a multivariate analysis has revealed a positive correlation with BMI, highly sensitive C reactive protein (hsCRP), and TG [ 137 ]. Three DMRs annotated to the sodium/hydrogen exchanger 1 (SLC9A1), solute carrier family 1 neutral amino acid transporter member 5 (SLC1A5), and trinucleotide repeat containing adaptor 6C (TNRC6C) genes significantly replicated across the two cohorts, providing possible useful predictive biomarkers [ 137 ]. However, the possible cause–effect relationship between methylation changes in these genes and CV risk needs to be determined.…”
Section: Epigenetics and Risk Stratification Of Cvds: Network Medicinmentioning
confidence: 99%